2016
DOI: 10.1021/acs.jpcb.6b00125
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Characterization of the H-Bonding and Stacking Potential of Two Nonstandard Nucleobases Expanding the Genetic Alphabet

Abstract: We report a quantum chemical characterization of the non-natural (synthetic) H-bonded base pair formed by 6-amino-5-nitro-2(1H)-pyridone (Z) and 2-aminoimidazo[1,2-a]-1,3,5-triazin-4(8H)-one (P). The Z:P base pair, orthogonal to the classical G:C base pair, has been introduced into DNA molecules to expand the genetic code. Our results indicate that the Z:P base pair closely mimics the G:C base pair in terms of both structure and stability. To clarify the role of the NO2 group on the C5 position of the Z base, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 81 publications
5
31
0
Order By: Relevance
“…Their implicit-solvent calculations predict effectively isoelectronic energies again (−15 kcal/mol and −15 kcal/mol). The same trends (−28 for each in the gas phase, −13 kcal/mol for each in implicit solvent representation), were observed in a second report, albeit for different functional, basis choice and implicit solvent model (19). …”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Their implicit-solvent calculations predict effectively isoelectronic energies again (−15 kcal/mol and −15 kcal/mol). The same trends (−28 for each in the gas phase, −13 kcal/mol for each in implicit solvent representation), were observed in a second report, albeit for different functional, basis choice and implicit solvent model (19). …”
Section: Resultssupporting
confidence: 74%
“…On the other hand, this same 16-bp oligonucleotide under low salt conditions gives a CD spectrum corresponding to B-form, that is similar to that of an oligonucleotide (5΄-CTTATGGGCCCATAAG-3΄) in which P:Z nucleobase pairs are replaced by G:C . A previous quantum mechanical study has addressed the stability of hydrogen-bonding in the Z:P pair finding it comparable to G:C (19). This same study compared base stacking of the Z-nitro group with another Z or P nucleobase as compared to Z with the nitro group replaced by an H atom and found the ZP/ZP or ZZ/PP stacking interactions to be more favorable (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 We, and others, 14,15 have therefore used these methods to demonstrate that stacking P:Z nucleobase pairs is energetically preferred to stacking G:C nucleobase pairs by approximately 2.0 kcal/mol, 21 primarily because of favorable electrostatic interactions between the electron-deficient Z ring and the π-electrons of the adjacent P nucleobase (Fig. 2).…”
Section: Quantum Mechanical Characterization Of P:z Stackingmentioning
confidence: 98%
“…To date, QM calculations have only been reported for the P:Z nucleobase pair. 14,15,21 Although high-level ab initio calculations suggest that the free energy of hydrogen bonding in the P:Z nucleobase pair is less favorable (1.4 kcal/mol) than for G:C in the gas-phase, 21 calculations that include the effects of solvation indicate that the presence of the Z-nitro group decreases the enthalpy of the hydrogen bonds in P:Z relative to those in G:C by 0.6 kcal/mol. 15,21 This finding is supported by recent biophysical studies in which the P:Z hydrogen bonding interactions were found to be stronger than natural or mispaired interactions involving either P or Z .…”
Section: Quantum Mechanical Characterization Of the P:z Pairmentioning
confidence: 99%